Dietary patterns of children living in slums and their associated factors: a cross-sectional study, 2019-2022 - Gabriela Rossiter Stux Veiga; Bruna Merten Padilha; Lídia Bezerra Barbosa; Thaysa Barbosa Cavalcante Brandão; Telma Maria de Menezes Toledo Florêncio; Marilia de Carvalho Lima (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To identify dietary patterns and analyze factors associated with the consumption profile of socially vulnerable children, Maceió, state of Alagoas, Brazil, August 2019 to December 2021. Methods This was a cross-sectional study; sociodemographic, anthropometric and food consumption variables were collected, factor analysis was used to identify dietary patterns; associations were analyzed using Poisson regression. Results Among the 567 children studied, two dietary patterns were identified, healthy and unhealthy; age ≥ 24 months (PR = 2.75; 95%CI 1.83;4.14), male gender (PR = 0.66; 95%CI 0.49;0.87) and maternal schooling ≤ 9 years (PR = 0.61; 95%CI 0.46;0.81) was higher in the healthy pattern; the unhealthy pattern was associated with age ≥ 24 months (PR = 1.02; 95%CI 1.01;1.03) and male gender (PR = 1.46; 95%CI 1.08;1.98). Conclusion The healthy pattern was more frequent in children aged ≥ 24 months, less frequent in male children and mothers with low level of schooling; children aged ≥ 24 months and males showed a higher prevalence of the unhealthy pattern.